SAK EMKM-Based Accounting Training to Improve MSME Financial Reporting and Tax Awareness - Sindik Widati; Ahmad Bukhori Muslim; Benny Oktaviano; Dwi Rahmania (Lentera Ilmu Nusantara, 2026)
Limited financial reporting skills and insufficient understanding of tax obligations remain major challenges affecting business governance and tax compliance among micro, small, and medium enterprises. This community service program aimed to improve participants' knowledge and skills in preparing financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities and to enhance their understanding of taxation. The program was conducted at Universitas Pelita Bangsa on May 8, 2026, involving 14 micro, small, and medium enterprise owners from Bekasi Regency. The implementation methods included socialization, training sessions, hands-on financial reporting practices, application of simple financial recording technology, mentoring, and evaluation activities. The results demonstrated an improvement in participants' understanding of transaction recording, income statement preparation, statement of financial position preparation, and tax obligations. Most participants were able to prepare simple financial statements and gained awareness of the importance of separating personal and business finances. In addition, participants showed increased awareness of tax compliance as an essential component of sound business governance. The program indicates that structured training and mentoring can effectively strengthen financial management competencies and support improved tax compliance among micro, small, and medium enterprises.